(untitled) (Studia Prawnicze / The Legal Studies, 2015)
Problematyka notyfikacji jest zagadnieniem stosunkowo nowym w polskiej doktrynie prawa. Zainteresowanie literatury procedurą notyfikacyjną wzrosło po ostatnich orzeczeniach polskich sądów, ale również Trybunału Sprawiedliwości Unii Europejskiej w głośnej sprawie Fortuna i inni. Ten ostatni wyrok dotyczący braku notyfikacji przepisów ustawy z dnia 19 listopada 2009 r. o grach hazardowych (Dz. U. Nr 201, poz. 1540, z późn. zm.) wywołuje wątpliwości w zakresie oceny jego skutków dla polskich sądów, które interpretują go w niejednolity sposób z uwagi na niejednoznaczne określenie tego, czy inkryminowane przepisy ustawy o grach hazardowych mają charakter przepisów technicznych, czy nie. Jakkolwiek w związku z przywołanymi orzeczeniami uwaga przedstawicieli doktryny koncentruje się na kwestiach związanych z notyfikacją przepisów i norm technicznych, to można dostrzec również wypowiedzi, w których następuje szersze ujęcie obowiązków notyfikacyjnych. The author provides an analysis of the issue who should be competent to the notification of the parliamentarian draft bills. The article examines meaning of the notification in different areas of law, particularly international and European Union law. Apart from general remarks on the meaning of notification in the context of principle of loyalty, the analysis shows the character of this institution in connection with the consequences of a breach of the due notification. The author focuses on three main types of the procedure of the notification: notification of the state aid, notification of the technical standards and regulations and notification of the draft legislative provisions falling within the European Central Bank’s field of competence. The analysis shows that there is no complex regulation in polish system of law according to the notification procedure. Due to the need to avoid the problems associated with the breach of the due notification author presents his view on the issue who should notify the parliamentarian draft bills and puts forward a number of arguments supporting the conception of the significant role of the sponsor of the bill in procedure of notification.